2023
DOI: 10.3390/biomedicines11051497
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Perspective on How Photobiomodulation May Influence Fatigue, Pain, and Depression in Inflammatory Bowel Disease: Beyond Molecular Mechanisms

Abstract: Background: Numerous mechanisms, mostly molecular, have been tested and proposed for photobiomodulation. Photobiomodulation is finding a niche in the treatment of conditions that have no gold-standard treatment or only partially effective pharmacological treatment. Many chronic conditions are characterised by symptoms for which there is no cure or control and for which pharmaceuticals may add to the disease burden through side effects. To add quality to life, alternate methods of symptom management need to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…As described by Santos et al [92], photobiomodulation traces back at least to Finsen who won the Nobel prize in Medicine and Physiology for his light-based treatment of both cutaneous tuberculosis and smallpox [93,94]. The term photobiomodulation has been become associated with therapy using non-ionizing light sources (e.g., LED, lasers, and broadband light) in the visible and infared spectrums [92,95]. The therapeutic frequencies encompass a range of approximately 600-1200 nm with different frequencies having different skin penetration capacities [92].…”
Section: Light and Radiation Frequency Modulation Of Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Santos et al [92], photobiomodulation traces back at least to Finsen who won the Nobel prize in Medicine and Physiology for his light-based treatment of both cutaneous tuberculosis and smallpox [93,94]. The term photobiomodulation has been become associated with therapy using non-ionizing light sources (e.g., LED, lasers, and broadband light) in the visible and infared spectrums [92,95]. The therapeutic frequencies encompass a range of approximately 600-1200 nm with different frequencies having different skin penetration capacities [92].…”
Section: Light and Radiation Frequency Modulation Of Microbiotamentioning
confidence: 99%
“…Table 3 illustrates examples of the effects of light on microorganisms [92,95,96,104,[109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126]. In a review of PBM and chronic kidney disease, the pathways of PBM facilitating correction of mitochondrial dysfunction as well as gut microbiome dysbiosis are main pathways to health improvement.…”
Section: Light and Radiation Frequency Modulation Of Microbiotamentioning
confidence: 99%
“…Taken together, these research results suggest that PBM can improve fatigue, depression, pain, and microbiome diversity in chronic disease. Despite this, there have been no trials or reviews of PBM in IBD to date apart from our group’s recent article on the mechanism of PBM in IBD [ 26 ]. This prospective, single-arm pilot study of PBM in youth with IBD will therefore assess the feasibility and preliminary efficacy of PBM in IBD.…”
Section: Photobiomodulation In Treatment Of Fatigue Depression and Painmentioning
confidence: 99%
“…The beneficial effects of PBM in reducing inflammation and edema, restoring blood flow, improving tissue healing, and inducing analgesia have been widely demonstrated in humans [ 16 , 17 , 18 ]. Moreover, there is also growing evidence that PBM may influence the microbiome [ 19 , 20 , 21 , 22 , 23 , 24 ]. Interestingly, Bicknell and colleagues demonstrated that PBM delivered to the abdomen of mice produced a significant change in the gut microbiome and, in humans, they observed a change in the microbiome in Parkinson patients after PBM treatment [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%